Reprezentacja wiedzy w diagnostycznym systemie ekspertowym - Pieczyński, Andrzej (1953- ) (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The synthesis of problem consist the integration of different form of knowledge representation for the complex industrial processes dignosis has been discussed.
Keywords: doradczy system ekspertowy; reprezentacja bazy wiedzy; reguły; filtry Kalmana; sieci neuronowe; zbiory rozmyte; modelowanie rozmyte; wydobywanie wiedzy z baz danych; hurtownie danych; integracja wiedzy; advisory expert system; knowledge base representation; rules; Kalman filters; neural networks; fuzzy sets; fuzzy modelling; knowledge discovery in databases; data warehouses; knowledge integration